Sustainable Landscape Construction: Materials and Products — Wood Preservatives - Gail Hansen (EDIS)
ENH1143, a 1-page fact sheet by Gail Hansen, lists several sustainable landscape construction techniques that help mitigate environmental damage and health concerns of wood preservatives. Includes references. Published by the UF Department of Environmental Horticulture, October 2009.